Segmentation of Malaysian ecotourists at Kinabalu National Park based on ecotourism attributes - Bidin, Sheena (2012)
Understanding ecotourists is an integral part in ecotourism marketing as it allows planners and marketers to design products based on the target market needs. Since domestic ecotourism is a blooming industry in Malaysia, information regarding the Malaysian ecotourist market segments is vital to enhance and assist the development of ecotourism. The main purpose of this study was to segment Malaysian ecotourist market into hard, structured and soft ecotourists using the fundamental ecotourism principles, as well as general trip characteristics associated with their ecotourism experience. With a sample of 403 Malaysian ecotourists in Kinabalu National Park, Sabah, a discriminant analysis was employed in this study to identify the three clusters of hard, structured and soft ecotourists. The results obtained in this study confirm that the domestic ecotourist segment in Malaysia comprises of hard, structured and soft ecotourists, which further corroborate to the findings of previous studies in the literature. Meanwhile, cross validations from the identified ecotourist segments found that 39 percent of the Malaysian ecotourist segments were identified as hard ecotourists, while 61 percent of the Malaysian ecotourists consisted of the structured and soft ecotourists segments. It is further acknowledged that majority of the 61 percent of the structured and soft ecotourists tend to portray travel characteristics towards the softer end of the ecotourism spectrum. The other purpose of this study was to ascertain the identified ecotourist segment preferences towards the selected attributes of eco-friendly accommodation, particularly the ecolodges. Recognizing that users of ecotourism accommodation would most likely be ecotourists, determining the preferences towards the attributes of eco-friendly accommodation is an important aspect in marketing, particularly in designing and implementing programmes that suit ecotourism accommodations. In this study, several variables of ecolodges, including the main principles of ecolodges, were taken into consideration for the purpose of getting a glimpse into the identified ecotourists’ segments preferences towards ecotourism accommodations. It was found that the hard ecotourists presented the same tendencies in adhering to the principles of ecotourism, whereby they gave higher ratings for several eco-friendly attributes as compared to the structured and soft ecotourists. Meanwhile, the hard ecotourists also rated significantly higher tendencies to prefer attributes measuring inclinations towards nature-based attractions (M=4.17) compared to the structured and soft ecotourists. On the contrary, the hard ecotourists also rated significantly lower in the attributes preferring services and comfort, as well as preferring the type of accommodations that are rather rustic and contain natural elements. The results of this study further acknowledge that the Malaysian ecotourist segments are not homogenous, and this further recommends the implications towards the design of programmes and accommodation packages based on the types of ecotourists, as well as the active implementation of environmental-friendly practices in ecotourism areas.